PROBLEM BASED LEARNING MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR KELAS VII A SEMESTER GENAP MATA PELAJARAN IPS DI SMP NEGERI 1 GIRIMARTO TAHUN PELAJARAN 2022/2023 - Prih Haryati (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
The aim of this research areto improbe the actives and skills the students of SMPN 1 Girimarto in understanding the material learning through Problem Based Learning (PBL). Especially this research are expected can improve the students skill in understanding the material learning, the student's skill are improve with the indicators: (1)75% students get 75 score, (2)75% students are motivated in the learning process, (3)75% students are condusive in the teching learning proses, (4)75% teachers have more experience and knowledge about teching technique. This research use descriptive comparative method. Technique or PBL model include: 1) identify the topic, 2) determine the aim of learning, 3) identify ing problems, 4) materi access. Based on the classroom action research above it can be concluded that PBL can improve the actives and students skill to understanding materil learning, and the used of PBL learning can improve the active and the result of the learning on VII A in the second semester SMPN1Girimarto in academic year 2022/2023.